Renewable Energy Cost Estimation on Smart On Grid Actuator Innovation for the Development of Alternative Rural Electricity - Andjar Prasetyo (The Indonesian Journal of Planning and Development, 2019)
Indonesia's target for using the energy mix through Renewable Energy (RE) is 22.5 percent in 2025. The steps taken are to optimize local energy use for electricity generation and select more efficient technologies that can reduce the cost of electricity supply. One of the pioneers carried out in the city of Magelang is the Smart on Grid Actuator (SOGA) system that converts sunlight into electrical energy. This study aims to calculate and analyze estimated costs by using the sun using SOGA System innovations. The research location in the Research and Development Agency of the City of Magelang focused on cost efficiency testing based on solar energy harvesting with SOGA. The survey on the use of SOGA innovation was conducted during October 2018 to obtain primary data. The approach to the results of previous research and theoretical approaches is intended as a reference, and secondary data complete the analysis of this study. Study analysis uses the Financial and Economic Benefits Photovoltaic Grid-Tied System projection (Utility-Based Rebate Formula). As a result, the SOGA system can reduce installed electricity costs by ± 330 USD per year and can be used for alternative rural energy development.